Language Politeness of Indonesian Language Education Study Program Students via Whatsapp Social Media: A Pragmatic Study - Aritonang, Devinna Riskiana; Dewi, Shoufi Nisma; Nurhaida, Nurhaida (Jurnal Hata Poda, 2025)
This study is entitled "Language Politeness of Indonesian Language Education Study Program Studentst hrough Whatsapp Social Media." This study aims to describe the language politeness of students and language violations when communicating with lecturers via short messages or WhatsApp chat. This research method use qualitative descriptive method. The subjects used in this study were students in semesters II, IV, and VI of the Indonesian Language Education Study Program, Faculty of Science and Teacher Training, Muhammadiyah University of South Tapanuli with atotal of 93 students. The data collection technique used in this study is the listening method followed by basic tapping techniques, advanced techniques, free listening techniques, classification and identification techniques. The listening method is carried out by listening, namely listening to the use of language contained in conversations between students and lecturers via WhatsApp media. The results of the study show that the level of language politeness of students when communicating with lecturers via WhatsApp chat media is obtained from50 data consisting of 36 compliance with language politeness and 14 violations of language politeness. The level of language politeness of students in the Indonesian Language Education Study Programat UMTS is stated to be politewitha percentage of compliance with language politeness of 72% and violations of language politeness of 28%.